THE INFLUENCE OF LEADERSHIP AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT MIDTOU ARYACOM FUTURES - Kawiswara, Mandra (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of leadership and compensation on the performance of employees of PT Midtou Aryacom Futures. The research method used in this research is descriptive with a quantitative approach. The population amounted to 35 people, so the sampling technique was used with the saturated sample method and the number of samples obtained in this study were 35 respondents. Data analysis techniques using multiple linear regression. The results showed that: (1) There is a positive and significant influence of leadership variables on the performance of employees of PT Midtou Aryacom Futures. This is evidenced by the value of tcount > ttable, namely 5.541 > 2.037 with a probability value (significance) = 0.000, which is below 0.005. (2) There is a positive and significant influence of compensation variables on the performance of employees of PT Midtou Aryacom Futures. This is evidenced by the value of tcount> ttable, namely 6.930> 2.037 with a probability value (significance) = 0.000, which is below 0.005. (3) There is a positive and significant influence of leadership and compensation variables on the performance of employees of PT Midtou Aryacom Futures. This is evidenced by the value of Fcount > Ftable, namely 26.422 > 3.29 with a probability value (significance) = 0.000, which is below 0.005